The factors that contribute to the increasing number of demand toward life insurance / Nurul Farhan Abd. Halim - Abd. Halim, Nurul Farhan (2011)
Life insurance has become one of the most important things in human life. Nowadays, Malaysian people realize the importance of Life Insurance to protect their life for an unexpected event. Based on the data that provided by Bank Negara Malaysia (BNM) and Life Insurance Association of Malaysia (LIAM), show that premium income has impressive growth year by year. The research objective of this study was to determine the factor that contributes to the increasing numbers of demand towards Life Insurance and to identify the most dominant factor that contribute to the increasing number of demand toward life insurance. The data set in this study was collected among residents of Klang Valley. The research design of this study was descriptive study and researcher use Convenience Sampling Method in order to distribute the questionnaire. The 80 respondents become the sample in this study by answering the questionnaires and to interpret the data, researcher use SPSS. The finding has showed that all independents variable (income level, marital status and education level) have significant relationship with the dependent variable (demand on Life Insurance).